Astrocytes: definition, appearance and general physiology 1 - Verkhratsky, Alexei (Henry Stewart Talks, 2022)
The birth of neuroglia, Astrocytes (the parenchymal astroglia), Definition, appearance, and general physiology of astrocytes, Physiology of astrocytes, Astrocytes express a remarkable variety of ion channels, Astrocytes express diverse types of receptors, The channels and receptors mediate their functions